Olvashatósági tesztek: elmélet és gyakorlat (Training and Practice : Journal of Educational Sciences, 2019)
Readibilty formulas are well known tools in the USA to measure the readibility of a text. These tools are mathematical objects to sign how easily a text can be read by different people. In the EU these tools are not popular, because they are designed for the English language. Readibilty formulas are used in schools, in the army and in healthcare to show that people can understand a whole text easily or not. In the background we can find psychological factors and education factors to determine and help the understanding of a text.